2017
DOI: 10.3389/fphys.2017.00213
|View full text |Cite
|
Sign up to set email alerts
|

Interference with Ca2+-Dependent Proteolysis Does Not Alter the Course of Muscle Wasting in Experimental Cancer Cachexia

Abstract: Protein hypercatabolism significantly contributes to the onset and progression of muscle wasting in cancer cachexia. In this regard, a major role is played by the ATP-ubiquitin-proteasome-dependent pathway and by autophagy. However, little is known about the relevance of the Ca2+-dependent proteolytic system. Since previous results suggested that this pathway is activated in the skeletal muscle of tumor hosts, the present study was aimed to investigate whether inhibition of Ca2+-dependent proteases (calpains) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Such a hypothesis was previously demonstrated in colon cancer cells [21], although convincing evidence in the skeletal muscle is lacking. In this regard, previous data reported that either proteasome [4] or calpain [22] inhibition do not improve cancer-induced muscle wasting, in agreement with the idea that targeting a specific proteolytic system likely leads to compensatory activation of the others, vanishing treatment effectiveness. The other way round, simultaneously blocking more than one proteolytic system likely results in potential cumulative side effects, considering the reported accumulation of p62 upon beclin-1 knock-down, although a phase 1 clinical trial using both proteasome and autophagy inhibitors was reported in patients with relapsed/refractory myeloma [23].…”
Section: Accepted Manuscript 14supporting
confidence: 78%
“…Such a hypothesis was previously demonstrated in colon cancer cells [21], although convincing evidence in the skeletal muscle is lacking. In this regard, previous data reported that either proteasome [4] or calpain [22] inhibition do not improve cancer-induced muscle wasting, in agreement with the idea that targeting a specific proteolytic system likely leads to compensatory activation of the others, vanishing treatment effectiveness. The other way round, simultaneously blocking more than one proteolytic system likely results in potential cumulative side effects, considering the reported accumulation of p62 upon beclin-1 knock-down, although a phase 1 clinical trial using both proteasome and autophagy inhibitors was reported in patients with relapsed/refractory myeloma [23].…”
Section: Accepted Manuscript 14supporting
confidence: 78%
“…Despite lysosomes and proteasome appear overactivated in conditions associated with muscle wasting, they are unable to directly break down myofibrillar proteins. To become available for degradation, the latter should undergo a preventive cleavage likely operated by calpains and/or caspases (91), whose activity in the muscle is indeed upregulated in both tumor-bearing animals (29,71,101) and cancer patients (124).…”
Section: Fig 1 Cancer Cachexia Is a Multifactorial Syndromementioning
confidence: 99%
“…Increased calpain expression was reported in the muscle of tumor-bearing animals [ 19 ], while rats transplanted with the Yoshida AH-130 hepatoma showed a progressive reduction of calpastatin levels and increased in vitro cleavage of specific fluorogenic substrates [ 20 ]. More recently, calpain activation was also demonstrated in mice bearing the C26 colon carcinoma [ 21 ]. Both increased or unchanged muscle calpain expression were reported in cancer patients [ 12 , 22 ].…”
Section: Protein and Amino Acid Metabolismmentioning
confidence: 99%
“…Despite the literature report data supporting the involvement of Ca 2+ -dependent proteolysis in the pathogenesis of cancer-induced muscle wasting, protein hypercatabolism was not downregulated in preparations of isolated muscles obtained from tumor-bearing animals and incubated in the presence of calpain inhibitors [ 19 , 33 , 34 ]. More recently, both pharmacological and genetic approaches aimed at inhibiting the Ca 2+ -dependent proteolytic system were not able to prevent or delay cancer-induced muscle wasting [ 21 ], although contrasting results were reported in this regard [ 35 ].…”
Section: Protein and Amino Acid Metabolismmentioning
confidence: 99%